Los derechos en “Dios y Estado” de Hans Kelsen = Rights in Hans Kelsen's God and State (2017)
This article deals with the analysis made by the famous jurist Hans Kelsen on the problem of sovereignty, tracing the convergences and divergences that lie in two models of sovereignty: the political and the religious. In this sense, some similarities between both types of sovereignty are shown from the point of view of the individual and psychological experience, thanks to common elements such as superiority, union with the community, hypostasis and personification, among others. This approach develops the purpose of the text: to elucidate why the notion of rights is central to the differentiation between the two types of sovereignty, thanks to the particular way in which the two types of sovereignty are expressed. of sovereignty, thanks to the particular way of connecting the concepts of authority, power and individual, in each of them, power and the individual, in each of them